Synthesis and Biocompatibility of Silicone Hydrogel Functionalized with Polysaccharide. (26th May 2015) - Jeong, Keun‐Seung; Kim, Ho‐Joong; Lim, Hwa‐Lim; Ryu, Geun‐Chang; Seo, Eun‐Sun; You, Nam‐Ho; Jun, Jin
<x xml:space="preserve">Abstract</x> A novel methacrylated polydimethylsiloxane was synthesized for the preparation of silicone hydrogel (SiHy). The SiHy was functionalized with polysaccharides such as hyaluronic acid and alginic acid by construction of an interpenetrating polymer network (IPN) structure composed of cross‐linked SiHy backbones and polysaccharide networks. The polysaccharide‐modified SiHys have proven to successfully reduce nonspecific protein adsorption and improve the surface hydrophilicity compared with unmodified SiHy.